Manajemen Keuangan Dalam Meningkatkan Pelayanan Persekutuan Doa: Indonesia - lase, erni; Karo Karo, Desire (STT INDONESIA MANADO, 2021)
Abstract: In general, people use money as a medium of exchange in buying and selling activities or so-called economic activities. Money is also one of the factors supporting a harmonious family where money can meet all the needs of the family or society. In particular, prayer fellowship activities are carried out in churches in Indonesia, in these activities there are several programs carried out, one of which is the determination of the treasury in these activities with the aim of (1) so that the congregation and readers can know good financial management in the Book of II Kings -King 12:10-12 correctly and correctly, (2) so that the congregation who participates in the Prayer Fellowship, in particular and other readers can improve their organizational structure by implementing financial management contained in the Book of II Kings 12:10-12, so that it can improve existing financial management, (3) to find out the role of a treasurer in managing finances in an organization, especially prayer groups so that finances can be well directed, money is functioned according to service needs, supports service activities and there is financial clarity that has been used so that the meaning of the treasury is it can manage financially well and in accordance with the Bible and the expectations of the members of the prayer group.